2012
DOI: 10.1186/1471-2121-13-18
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive activity enhances central carbon metabolism and bioenergetics in myeloid-derived suppressor cells in vitro models

Abstract: BackgroundThe tumor microenvironment contains a vast array of pro- and anti-inflammatory cytokines that alter myelopoiesis and lead to the maturation of immunosuppressive cells known as myeloid-derived suppressor cells (MDSCs). Incubating bone marrow (BM) precursors with a combination of granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin-6 (IL-6) generated a tumor-infiltrating MDSC-like population that impaired anti-tumor specific T-cell functions. This in vitro experimental approach was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 47 publications
(65 reference statements)
3
65
1
Order By: Relevance
“…Hammami, et al have shown that in mice, glycolysis increased concurrently with increased Arg1 activity in MDSC. Interestingly, they also note that AMP-activated protein kinase (AMPK) was activated, which normally drives metabolism towards oxidative phosphorylation [98]. In support of this finding, tumor-infiltrating MDSC increased fatty acid uptake and FAO.…”
Section: The Mechanisms Regulating the Myeloid Cell Function And Diffmentioning
confidence: 91%
“…Hammami, et al have shown that in mice, glycolysis increased concurrently with increased Arg1 activity in MDSC. Interestingly, they also note that AMP-activated protein kinase (AMPK) was activated, which normally drives metabolism towards oxidative phosphorylation [98]. In support of this finding, tumor-infiltrating MDSC increased fatty acid uptake and FAO.…”
Section: The Mechanisms Regulating the Myeloid Cell Function And Diffmentioning
confidence: 91%
“…Our data using in vitro -derived BM-MDSCs suggest that G-CSF or GM-CSF may also induce FAO (data not shown). A previous study showed that GM-CSF and IL6, instead, upregulate AMPK and glycolysis in BM-MDSCs (40). Recent reports suggest that lactic acid present in high concentrations in the tumor microenvironment can activate MDSCs (29, 41); however, its role in inducing FAO is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α may also be stabilized by the lactic acid that is produced by aerobic glycolysis (Warburg effect) in cancer cells (36). Alternatively, lactic acid can be actively produced in immune-regulatory myeloid cells by cytokine-activated, anerobic glycolysis (28,37).…”
Section: Mdscs and Tams Results From Altered Myelopoiesismentioning
confidence: 99%